2013
DOI: 10.7567/jjap.52.05ec01
|View full text |Cite
|
Sign up to set email alerts
|

Layer Transfer and Simultaneous Crystallization Technique for Amorphous Si Films with Midair Structure Induced by Near-Infrared Semiconductor Diode Laser Irradiation and Its Application to Thin-Film Transistor Fabrication

Abstract: A novel layer transfer and simultaneous crystallization of amorphous silicon (a-Si) films induced by near-infrared semiconductor-diode-laser (SDL) irradiation has been investigated. The a-Si films supported by narrow quartz columns on a starting quartz substrate and a counter substrate [glass and poly(ethylene terephthalate)] were in face-to-face contact, and an SDL irradiated the a-Si films with midair structure. After SDL irradiation, the Si films were completely transferred and crystallized simultaneously o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In our previous work, amorphous silicon (a-Si) films with a midair cavity were transferred to glass substrates and simultaneously crystallized by near-infrared semiconductor diode laser (SDL) irradiation. 26) It was shown that Si layers as large as 10 © 10 mm 2 area can be transferred using a Si film with a midair cavity (by controlling the position where quartz columns are formed). If the Si film can be "locally and repeatedly" transferred from a single starting substrate to a predetermined position on several different substrates by this transfer technique, the Si-use efficiency could be significantly improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, amorphous silicon (a-Si) films with a midair cavity were transferred to glass substrates and simultaneously crystallized by near-infrared semiconductor diode laser (SDL) irradiation. 26) It was shown that Si layers as large as 10 © 10 mm 2 area can be transferred using a Si film with a midair cavity (by controlling the position where quartz columns are formed). If the Si film can be "locally and repeatedly" transferred from a single starting substrate to a predetermined position on several different substrates by this transfer technique, the Si-use efficiency could be significantly improved.…”
mentioning
confidence: 99%
“…Therefore, although the absorption of near-infrared light in the Si film is less than that of ultraviolet (UV) light, the Si film can be heated efficiently. 26) After the a-Si films with the midair cavity were irradiated by SDL at P of 60 W and scanning speed (v) of 2 mm/s, the patterned Si films were transferred to a counter glass substrate. Here, the Si film transfer from a single starting quartz substrate to two different glass substrates was carried out sequentially.…”
mentioning
confidence: 99%
“…Quartz columns (with an area of 1 © 1 µm 2 ) were formed by controlling the duration of dipping in hydrofluoric acid. 11) The starting quartz substrate thus prepared and the counter-PET substrates were placed in close face-to-face contact, and 8 µL of pure water was sandwiched between them to form a water layer between the a-Si films and the PET substrates and to fill the midair cavity (see Fig. 1).…”
mentioning
confidence: 99%
“…13,14 In a previous work, amorphous-silicon films with a midair cavity were simultaneously transferred to polyethylene terephthalate (PET) substrates and crystallized by using near-infrared semiconductor-diode-laser irradiation. 22 As for the important point of that work, it was shown that local layers of various shapes can be transferred by using Si film with a midair cavity (by controlling the position where quartz columns are formed). In the present work paper, a low-temperature technique for locally transferring siliconon-insulator (SOI) layers (supported by SiO 2 columns) from a starting SOI wafer by using meniscus force (without use of a laser) is proposed, and the performance of flexible MOSFETs fabricated by using a c-Si film transferred by this technique is verified experimentally.…”
mentioning
confidence: 99%